PENGARUH KOMPETENSI, KEPUASAN KERJA DAN EMPLOYEE ENGAGEMENT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA SEKRETARIAT UTAMA BADAN PANGAN NASIONAL REPUBLIK INDONESIA - Alfriano Farrel Ridhyoza (2022)
The type of research conducted by researchers is quantitative research which aims to determine the effect of competence on organizational citizenship behavior, the effect of job satisfaction on organizational citizenship behavior, the effect of employee engagement on organizational citizenship behavior. As well as the effect of competence, job satisfaction and employee engagement partially on organizational citizenship behavior. This research is a quantitative data with primary data sources. The population of this research is the Main Secretariat of the National Food Agency of the Republic of Indonesia. The sample used amounted to 60 respondents. The sampling technique uses non-probability sampling with purposive sampling method. Data collection was carried out by this study with an online questionnaire using the Google Form facility. This study uses the SEM method with the software used is SmartPls 3.0. This study obtained the results: competency variables had a positive and significant effect on organizational citizenship behavior with an original sample value of 0.492. Job satisfaction has a positive and significant effect on organizational citizenship behavior with an original sample value of 0.223. Employee engagement has a positive and significant effect on organizational citizenship behavior with an original sample value of 0.282. Competence, job satisfaction and employee engagement partially to organizational citizenship behavior.